Mass Spectrometry-Based Lipidomics of Brown Adipose Tissue and Plasma of New-Born Lambs Subjected to Short-Term Cold Exposure - Graña-Baumgartner A; Dukkipati VSR; Biggs PJ; Kenyon PR; Blair HT; Lopez-Villalobos N; Ross AB (MDPI (Basel, Switzerland), 2022)
During cold exposure, brown adipose tissue (BAT) holds the key mechanism in the generation of heat, thus inducing thermogenic adaptation in response to cooler environmental changes. This process can lead to a major lipidome remodelling in BAT, where the increase in abundance of many lipid classes plays a significant role in the thermogenic mechanisms for heat production. This study aimed to identify different types of lipids, through liquid chromatography-mass spectrometry (LC-MS), in BAT and plasma during a short-term cold challenge (2-days), or not, in new-born lambs. Fifteen new-born Romney lambs were selected randomly and divided into three groups: Group 1 (n = 3) with BAT and plasma obtained within 24 h after birth, as a control; Group 2 (n = 6) kept indoors for two days at an ambient temperature (20-22 °C) and Group 3 (n = 6) kept indoors for two days at a cold temperature (4 °C). Significant differences in lipid composition of many lipid categories (such as glycerolipids, glycerophospholipids, sphingolipids and sterol lipids) were observed in BAT and plasma under cold conditions, compared with ambient conditions. Data obtained from the present study suggest that short-term cold exposure induces profound changes in BAT and plasma lipidome composition of new-born lambs, which may enhance lipid metabolism via BAT thermogenic activation and adipocyte survival during cold adaptation. Further analysis on the roles of these lipid changes, validation of potential biomarkers for BAT activity, such as LPC 18:1 and PC 35:6, should contribute to the improvement of new-born lamb survival. Collectively, these observations help broaden the knowledge on the variations of lipid composition during cold exposure.
Keywords: BAT; lambs; lipidomics; mass spectrometry; thermogenesis